A study of the attitudes of students and their parents on human population education - Cadena, Elisa Celia Villalobos 1926- ([Quezon City s.n.], 1974)
The focus of this study is based on the attitudes of selected biology students and their parents on population education. It is an exploratory study that tells whether the attitudes of students on human population changed with the use of "Human Population for Secondary Students" as a teaching material prepared by the UP Science Education Center or not.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Population -- study and teaching